Phosphorylation of Ribosomal Protein RPS6 Integrates Light Signals and Circadian Clock Signals - Enganti, Ramya; Cho, Sung Ki; Toperzer, Jody D.; Urquidi-Camacho, Ricardo A.; Cakir, Ozkan S.; Ray, Alexandria P.; Abraham, Paul E.; Hettich, Robert L.; von Arnim, Albrecht G. (Frontiers in Plant Science, 2018)
The translation of mRNA into protein is tightly regulated by the light environment as well as by the circadian clock. Although changes in translational efficiency have been well documented at the level of mRNA-ribosome loading, the underlying mechanisms are unclear. The reversible phosphorylation of ribosomal protein of the small subunit 6 (RPS6) has been known for forty years, but the biochemical significance of this event remains unclear to this day. Here, we confirm using a clock-deficient strain of Arabidopsis thaliana that RPS6 phosphorylation (RPS6-P) is controlled by the diel light-dark cycle with a peak during the day. Strikingly, when wild-type, clock-enabled, seedlings that have been entrained to a light-dark cycle are placed under free-running conditions, the circadian clock drives a cycle of RPS6-P with an opposite phase, peaking during the subjective night. We show that in wild-type seedlings under a light-dark cycle, the incoherent light and clock signals are integrated by the plant to cause an oscillation in RPS6-P with a reduced amplitude with a peak during the day. Sucrose can stimulate RPS6-P, as seen when sucrose in the medium masks the light response of etiolated seedlings. However, the diel cycles of RPS6-P are observed in the presence of 1% sucrose and in its absence. Sucrose at a high concentration of 3% appears to interfere with the robust integration of light and clock signals at the level of RPS6-P. Finally, we addressed whether RPS6-P occurs uniformly in polysomes, non-polysomal ribosomes and their subunits, and non-ribosomal protein. It is the polysomal RPS6 whose phosphorylation is most highly stimulated by light and repressed by darkness. These data exemplify a striking case of contrasting biochemical regulation between clock signals and light signals. Although the physiological significance of RPS6-P remains unknown, our data provide a mechanistic basis for the future understanding of this enigmatic event.